Autism Spectrum Disorder: the Present Perspective - Chaudhuri, S; Chatterjee, N (Journal of College of Medical Sciences-Nepal, 2015)
The last decade has witnessed a surge of awareness about autism among the public and professionals. Much revealing research is being done on this issue and the knowledge base has improved substantially and a set of professionals are specializing on the subject, focusing on its causative factors and management. Autism being a disorder stemming from early childhood and the prevalence rate rising alarmingly over the years, Pediatricians are expected to play a vital role in early detection and early intervention in management of the problem. But, unfortunately, autism is not yet considered to be under the purview of pediatricians. As pediatricians, we are often perplexed when faced with such a different child in our office and either overlook the problem or hurry to hand him over to a psychiatrist, not trying to really identify and understand the problem as a medical entity ourselves. Hence better awareness among pediatricians is the need of the day. As specialists have worked with autism over the decades, it has become clear that: autism is a disorder that involves early development, presently there is no medical answer to autism, and the only management strategy hinges largely on effective training. The earlier the training begins the better it is for the child. It is of paramount importance to start training and bring about changes by the time the child is 18 months old. This throws up interesting new challenges to the profession of pediatrics. To identify the early warning signs of autism, it is important that Pediatricians are able to recognize the signs and symptoms of autistic spectrum disorders (ASD), have a strategy for assessing them systematically, be familiar with available tools for screening as well as developmental and educational resources. DOI: http://dx.doi.org/10.3126/jcmsn.v10i3.12775 Journal of College of Medical Sciences-Nepal, 2014, Vol-10, No-3, 37-47